If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11 = -2x + 1 + 5x Reorder the terms: -11 = 1 + -2x + 5x Combine like terms: -2x + 5x = 3x -11 = 1 + 3x Solving -11 = 1 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -11 + -3x = 1 + 3x + -3x Combine like terms: 3x + -3x = 0 -11 + -3x = 1 + 0 -11 + -3x = 1 Add '11' to each side of the equation. -11 + 11 + -3x = 1 + 11 Combine like terms: -11 + 11 = 0 0 + -3x = 1 + 11 -3x = 1 + 11 Combine like terms: 1 + 11 = 12 -3x = 12 Divide each side by '-3'. x = -4 Simplifying x = -4
| 19z+31=26z-74 | | 2(3-y)=4y+9 | | 8w-3a=36 | | (3p-7)+(5p-6)=0 | | 3x-12-2x=90 | | 5(p+2)=6(p-1) | | 5(6+x)=7(2-4) | | 4(3x+2)=15x+3-3x+5 | | 6x+6+5=13-2+6 | | 5(p+2)=6(y-1) | | 2x+33+5x-15=90 | | (3u+5)(u+7)= | | 3000+150.99w=6019.80 | | 4x=6y+14 | | -100+1x+7x=58 | | 50c=5 | | 4-9=x | | 200m-75m+61750=65650-200m | | (10g-18)=2 | | 3x+6=5x-x-1 | | x-24=111 | | 5m-2m+8+3m=20 | | X+15=76 | | (3u+5)(7+u)= | | -9-6=x | | 4a=72 | | 3(d+12)=8 | | x+0.21=488.22 | | 4+8(x-9)=8-8(x-2) | | -16+10=m-8 | | 3(x-1)-x=9 | | 200-40m+.15m=58 |